Optimization of inter-helix spacing for helical piles in sand - Kang Shao; Qian Su; Junwei Liu; Kaiwen Liu; Zhipeng Xiong; Tengfei Wang (Journal of Rock Mechanics and Geotechnical Engineering, 2022)
The optimization of the inter-helix spacing is a key issue of the axial bearing capacity of helical piles. In this paper, based on the cavity expansion, an analytical approach considering the small-strain stiffness, strength, compressibility and stress level of sand around the helical pile was proposed to analyze the influence zone of the helices to determine the optimal inter-helix spacing in sand. The calculation results of the proposed method were verified using the centrifuge test data and finite element analysis for helical pile in Congleton HST95 sand. They were also compared with those using the Meyerhof pile foundation theory. The results show that the optimal inter-helix spacing based on Meyerhof pile foundation theory differs significantly from the measurement. The range of the influence zone for the helices in sand calculated by the cavity expansion theory matches with the data from literature. The calculation results with the proposed method are consistent with the range of the optimal spacing ratio inferred in the centrifuge tests. The results based on the two-dimensional (2D) finite element model (FEM) are also basically consistent with the calculated analytical solution.